Avaliação do efeito da corrosão em juntas sobrepostas da liga AL6060-T5 soldadas pelo processo FSSW - (:unkn) unknown (Universidade Federal do Pampa, 2021)
Corrosion is a spontaneous process that occurs in all materials. This process is evidenced in metallic materials used in industry in general, as they have an energy differential when compared to their compounds found in nature. Thus, studying the behavior of the mechanical and chemical properties of metallic materials is fundamental to prevent failures. Aluminum alloys are one of the materials that have been used in the automotive and aerospace industry because they present a set of excellent properties such as: low density, corrosion resistance, high mechanical resistance, among others. In 2001, a new welding process, known as FSSW (Friction Stir Spot Welding) promotes union with better metallurgical properties compared to conventional processes. The plastic deformation and the increase in temperature cause microstructural changes in the regions of the welded joint, which, according to the literature, can present different resistance to corrosion. In this work, the corrosion resistance of Al6060-T5 alloy welded joint was evaluated by the FSSW process. For that, the samples were submitted to immersion test in 3.5% NaCl, at room temperature, for 1008h. Every 336h, a set of samples was removed, its PCA was evaluated and a shear test was performed, in addition to the hardness profile, analysis of the phases by X-Ray Diffraction. SEM analysis was performed, where corrosion was observed in the precipitated MgSi and corrosion products, in addition to the beginning of pitting corrosion in one of the evaluated samples. In the EDS, the chemical characterization of the weld regions was carried out, where an increase in the percentage of oxygen was noted, related to the electrochemical activity in the welded joint. Corrosive activity was identified in the mixing zone of all samples submitted to the immersion corrosion test. In global electrochemical tests, it was identified regions closer to the center of the weld have a higher corrosion rate, due to the presence of precipitated MgSi that had an anodic character, which trigger the corrosion process. Even so, the loss in the corrosion rate is small, and welded joints were resistant to the conditions imposed in this work.
Keywords: Engenharia; Alumínio - Corrosão; Metais - Propriedades mecânicas; Engineering; Aluminum - Corrosion; Metals - Mechanical properties; CNPQ::ENGENHARIAS